PENENTUAN HARGA POKOK PRODUKSI TERHADAP LABA USAHA; STUDI KASUS PADA UMKM DOUGHNUT DREAMLAND - Komang Tri Wahyuni (Nirta Learning Centre, 2024)
This research is a case study which aims to determine the determination of the cost of production towards business profits. Determining the cost of production uses two methods, namely full costing and variable costing, which is then analyzed for its effect on sales profits. In the research, the data used are primary data and secondary data. Primary data is obtained from direct observations of objects to obtain precise data as well as the results of interviews with business actors. Secondary data is obtained through company documents regarding data related to the cost of production which will affect the profits generated from the business. In this research, the approach taken by the author is a descriptive qualitative and quantitative approach, where this research describes the comparison of full costing and variable costing basic production prices and their influence on company profits. The object used in research at the UMKM Donut Dreamland is located in Denpasar, a home-based business operating in the culinary sector. The problem solving in this research is by calculating and analyzing the elements of production costs (manufacturing costs) such as direct raw material costs, direct labor and factory overhead costs, then determining the cost of production based on the full costing and variable costing methods, which are then analyzed for their effect on operating profit.